Quantifying the COVID-19 Impact on Inbound Tourism: An Empirical Examination Through the Lens of Transfer Function Analysis - Yugang He (SAGE Open)
This study provides a detailed examination of the intricate relationship between confirmed COVID-19 cases in South Korea and their impact on the nation’s inbound tourism. We utilize a robust mathematical framework, deploying a constructed transfer function model, to elucidate the dynamics of this socioeconomic phenomenon. Our findings reveal a tangible pattern: an increase of 1% in COVID-19 cases in South Korea corresponds to an approximate decrease of 0.071% in inbound tourism in the subsequent month. The consistency between the applied mathematical model and the derived empirical results underscores the reliability and utility of our chosen model. Moreover, it fortifies the argument for employing mathematical tools in the exploration of complex, dynamic socioeconomic relationships. Our research illuminates the critical role of mathematical reasoning and transfer functions in empirical research, particularly in the context of a global pandemic’s impact on a nation’s tourism industry. This study thereby lays the groundwork for further research employing mathematical modeling to comprehend dynamic phenomena across various research fields.